2019
DOI: 10.1002/ange.201907380
|View full text |Cite
|
Sign up to set email alerts
|

A Camptothecin‐Grafted DNA Tetrahedron as a Precise Nanomedicine to Inhibit Tumor Growth

Abstract: Most chemotherapeutics are hydrophobic molecules and need to be converted into hydrophilic form before administration. Based on the excellent hydrophilicity and programmability of DNA, now, a general strategy to construct a precise drug‐containing DNA framework for cancer treatment is reported. In this novel drug delivery system, carbonethyl bromide‐modified camptothecin (CPT) is employed to directly react with phosphorothioate (PS) modified DNAs, resulting in the formation of chemotherapeutics‐grafted DNAs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Mosaic modification means that functionalized molecules or groups are embedded in the double helix structure of TDN by conjugation, such as SYBR Green I [ 25 ] and other dyes [ 24 ] for fluorescent labelling, or anticancer drugs [ 23 , 31 33 , 42 ], and etc. DOX inhibits tumor growth by inserting DNA double strands to interfere with macromolecular biosynthesis [ 65 ].…”
Section: Functional Modification Of Tdnmentioning
confidence: 99%
See 3 more Smart Citations
“…Mosaic modification means that functionalized molecules or groups are embedded in the double helix structure of TDN by conjugation, such as SYBR Green I [ 25 ] and other dyes [ 24 ] for fluorescent labelling, or anticancer drugs [ 23 , 31 33 , 42 ], and etc. DOX inhibits tumor growth by inserting DNA double strands to interfere with macromolecular biosynthesis [ 65 ].…”
Section: Functional Modification Of Tdnmentioning
confidence: 99%
“…Meanwhile, experiments in vitro and in vivo showed that ANG-TDN could effectively cross the blood–brain barrier and precisely target U87MG human glioblastoma xenograft in nude mice. It had also been reported that siRNA or chemotherapy drugs can be loaded to TDN by cantilever modification [ 28 , 33 ], and that exchanging the hydrogen bonds of branched DNA structures for covalent bonds can further enhance TDN stability.…”
Section: Functional Modification Of Tdnmentioning
confidence: 99%
See 2 more Smart Citations
“…Such carboxylate CPT is mainly cleared by the kidneys and causes hemorrhagic cystitis and myelotoxicity, which caused the suspension of the clinical trials (Thomas et al., 2004). To address these challenges, strategies to overcome the aqueous insolubility and poor chemical instability of unmodified CPT remain a research hotspot in the recent scientific literatures (Alibolandi et al., 2017; Tian et al., 2017; Zhan et al., 2017; Li et al., 2018a; Dong et al., 2019; Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%